PENGEMBANGAN KELEMBAGAAN PENGGUNAAN LAHAN DI DAS CATUR KABUPATEN MADIUN - Khabibi Nurrofi' Pratama; Kukuh Murtilaksono; Hendrayanto Hendrayanto (TATALOKA, 2017)
Land use over its capability led to a watershed criticality. It was hypothesized by a lack of coordination in formulation and implementation of land use institution in watershed management. Catur watershed is one of critical watershed in Indonesia. This study aimed to formulate the development strategies of land use institution in Catur watershed. Institution analysis and development (IAD) framework was used to formulate it. The results showed land use problems in managing Catur watershed were 1) the overlap in determination of area function, 2) lack of socialization and supervision in implementing the regulation, and 3) a forum of coordination that has not been effective in accommodating the interests of each actors. Therefore, need an identification and involvement all the actors on conference of development planning (Musrenbang) to achieve a good governance.